2018
DOI: 10.1063/1.5022653
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the spectral energy cascade in turbulent channel flow

Abstract: An analysis of the spectral turbulent kinetic energy budget in a fully developed turbulent plane channel flow is performed. Direct numerical simulation data are evaluated at friction Reynolds numbers Re τ of 180 and 1000. The analysis is focused on the influence of the Reynolds number on the spectral cascade of energy and the corresponding energy cascade in physical space in the presence of inhomogeneity and anisotropy. The turbulent kinetic energy distribution is compared for both Reynolds numbers, and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Using direct numerical simulations, the energy exchanges associated with turbulence kinetic energy have been investigated in channel flows for various friction Reynolds number: 180 [33,46,1,25,64,38], 395 [46,1], 550-640 [46,16,1,25], 950-1000 [25,38], 2000 [24,25] and 5200 [38]. The spectral turbulence kinetic energy budget has been studied for the friction Reynolds numbers 170-210 [18,7,43,54,2], 500-615 [43,37,54], 900-1000 [43,37,2] and 5200 [37]. Andrade et al [2] showed that the spectral range of energy exchanges is broader at higher Reynolds number due to an increase in the low wavenumber scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using direct numerical simulations, the energy exchanges associated with turbulence kinetic energy have been investigated in channel flows for various friction Reynolds number: 180 [33,46,1,25,64,38], 395 [46,1], 550-640 [46,16,1,25], 950-1000 [25,38], 2000 [24,25] and 5200 [38]. The spectral turbulence kinetic energy budget has been studied for the friction Reynolds numbers 170-210 [18,7,43,54,2], 500-615 [43,37,54], 900-1000 [43,37,2] and 5200 [37]. Andrade et al [2] showed that the spectral range of energy exchanges is broader at higher Reynolds number due to an increase in the low wavenumber scales.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral turbulence kinetic energy budget has been studied for the friction Reynolds numbers 170-210 [18,7,43,54,2], 500-615 [43,37,54], 900-1000 [43,37,2] and 5200 [37]. Andrade et al [2] showed that the spectral range of energy exchanges is broader at higher Reynolds number due to an increase in the low wavenumber scales. Studies of energy exchanges have also been carried out in more complex wall-bounded geometries [6,54,44].…”
Section: Introductionmentioning
confidence: 99%
“…The form of the velocity field is altered and the flow field becomes more complex. Due to this complexity added to the velocity field, the flow presents inhomogeneity and anisotropy that are responsible for the generation of an energy transfer in the physical space, where the energy sources will behave differently depending on the distance from the wall [102,44,17,28,27,114,4].…”
Section: Large Eddy Simulationmentioning
confidence: 99%
“…More details about these behavior can be found in Sec. 2.3 and Andrade et al [4]. The hypothesis of alignment between τ and filtered rate-of-strain tensor ( S) is only possible to estimate a correctly general mean drain of energy from the resolved scales if the grid is sufficiently fine to resolve the SGS anisotropy.…”
Section: Mathematical Formulation and The Closure Problemmentioning
confidence: 99%
See 1 more Smart Citation